Validation and implementation of a direct RT-qPCR method for rapid screening of SARS-CoV-2 infection by using non-invasive saliva samples. (September 2021) - Brotons, Pedro; Perez-Argüello, Amaresh; Launes, Cristian; Torrents, Francesc; Subirats, Maria Pilar; Saucedo, Jesica; Claverol, Joana; Garcia-Garcia, Juan Jose; Rodas, Gil; Fumado, Vicky; Jordan, Iolanda; Gratacos, Eduard; et al.
Highlights: Saliva can be self-collected easily and safely for SARS-CoV-2 diagnostics. Direct RT-qPCR allows heat-treated virus inactivation without extraction reagents. Saliva-based direct RT-qPCR is sensitive and specific to detect SARS-CoV-2 RNA. This simple, fast method can be scaled up for SARS-CoV-2 community-wide screening. Abstract: Objective: To validate and implement an optimized screening method for the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA combining use of self-collected raw saliva samples, single-step heat-treated virus inactivation and RNA extraction, and direct RT-qPCR. Methods: This was a three-phase study conducted in Barcelona (Spain) during June to October, 2020. The three phases were (1) analytical validation against standard RT-qPCR in saliva samples; (2) diagnostic validation against standard RT-qPCR using paired saliva–nasopharyngeal samples obtained from asymptomatic teenagers and adults in a sports academy; and (3) pilot screening of asymptomatic health workers in a tertiary hospital. Results: In phase 1, the detection yield of the new method was comparable to that of standard RT-qPCR. In phase 2, the diagnostic sensitivity and specificity values in 303 self-collected saliva samples were 95.7% (95% confidence interval 79.0–99.2%) and 100.0% (95% confidence interval 98.6–100.0%), respectively. In phase 3, only 17 (0.6%) of the saliva samples self-collected by 2709 participants without supervision were invalid. The rapid analytical workflow with the new method (up to 384 batched samples could be processed in less than 2 hours) yielded 24 (0.9%) positive results in the remaining 2692 saliva samples. Paired nasopharyngeal specimens were all positive by standard RT-qPCR. Conclusions: Direct RT-qPCR on self-collected raw saliva is a simple, rapid, and accurate method with potential to be scaled up for enhanced SARS-CoV-2 community-wide screening.